Indonesian online learning system evaluation framework based on UTAUT 2.0 - Dwiyanto, Felix Andika; Elmunsyah, Hakkun; Yoto, Yoto (Association for Scientific Computing Electrical and Engineering, 2020)
This study aims to propose an evaluation of Indonesian online learning system which known as SPADA. This system accommodate an online learning for teacher profession education program which known as PPG. The system evaluation is using unified theory of acceptance and use of technology 2 (UTAUT2) model with a few adjustments. This study provide an information such as required variables to evaluate the system and research design on SPADA. The proposed evaluation model using seven main constructs of UTAUT 2.0 and its influence on behavioral intention and use behavior. The data obtained from several questionnaires related to the variable and analyzed with path analysis technique. Moreover, this proposed study is expected can be as reference to conduct a similar study related to the system evaluation.